2022
DOI: 10.1159/000523741
|View full text |Cite
|
Sign up to set email alerts
|

Shengxuebao Mixture for Iron Deficiency Anemia: A Meta-Analysis and Systematic Review

Abstract: Objective Traditional Chinese medicine Shengxuebao Mixture (SXBM) has been approved for treating iron deficiency anemia (IDA) in China. This study aimed to collect evidence and quantify the effect of SXBM on IDA. Methods Seven online databases were surveyed up to July 13, 2021. Randomized controlled trials in which SXBM was combined with conventional therapies to treat IDA and compared with placebo or conventional therapies were included in the study. The red blood cell (RBC) count, hemoglobin (Hb) level, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Our previous meta-analysis study has confirmed that SXBM is indeed effective in the treatment of IDA. [ 8 ] But the molecular mechanism of traditional Chinese medicine in the treatment of iron deficiency anemia still lacks modern scientific research. Recently, network pharmacology has gained worldwide prominence.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous meta-analysis study has confirmed that SXBM is indeed effective in the treatment of IDA. [ 8 ] But the molecular mechanism of traditional Chinese medicine in the treatment of iron deficiency anemia still lacks modern scientific research. Recently, network pharmacology has gained worldwide prominence.…”
Section: Introductionmentioning
confidence: 99%